2020
DOI: 10.3389/fnins.2020.00290
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Imagined and Spoken Phrases From Non-invasive Neural (MEG) Signals

Abstract: Speech production is a hierarchical mechanism involving the synchronization of the brain and the oral articulators, where the intention of linguistic concepts is transformed into meaningful sounds. Individuals with locked-in syndrome (fully paralyzed but aware) lose their motor ability completely including articulation and even eyeball movement. The neural pathway may be the only option to resume a certain level of communication for these patients. Current brain-computer interfaces (BCIs) use patients' visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 73 publications
(108 reference statements)
1
50
0
Order By: Relevance
“…Fourth-order Daubechies were used to achieve the results presented in [56] and were therefore used here. A feature vector was constructed using the RWE of decomposition levels D2 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32), D3 (8-16 Hz), D4 (4-8 Hz), D5 (2-4 Hz), and A5 (<2 Hz), for each channel. This resulted in a 30-element feature vector for each trial.…”
Section: Benchmark Machine Learning Classifiersmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth-order Daubechies were used to achieve the results presented in [56] and were therefore used here. A feature vector was constructed using the RWE of decomposition levels D2 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32), D3 (8-16 Hz), D4 (4-8 Hz), D5 (2-4 Hz), and A5 (<2 Hz), for each channel. This resulted in a 30-element feature vector for each trial.…”
Section: Benchmark Machine Learning Classifiersmentioning
confidence: 99%
“…One recent study has demonstrated the potential for spoken sentences to be synthesized from neural activity [ 14 ] and another has shown speech reconstruction directly from the auditory cortex while subjects listened to overt speech [ 15 ]. Non-invasive studies using magnetoencephalogram [ 16 ] and EEG [ 17 ] have demonstrated potential for decoding speech using these technologies. Several studies have used the advantage of non-invasive recording through EEG to investigate imagined speech as a communicative paradigm for BCIs (e.g., [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]).…”
Section: Introductionmentioning
confidence: 99%
“…The signals were of 1 kHz sampling frequency, from which the first two detail coefficients (d respectively. Considering the effectiveness of db-4 wavelet in increased SNR and decoding performance in our prior works [12], [47], [66] and its use in other decoding studies [26], we implemented this denoising and decomposing step prior to decoding. The use of wavelets to generate distinct MEG brainwaves has been shown previously [67]- [69].…”
Section: A Feature Extractionmentioning
confidence: 99%
“…Unfortunately, MEG requires expensive superconducting quantum interference devices operating in appropriate magnetically shielded rooms. Thus, MEG has been mostly used in neuroimaging and studies, although recently some attempts have been done in using this technique for silent speech recognition [198].…”
Section: ) Brain Activity Sensorsmentioning
confidence: 99%